2009
DOI: 10.1111/j.1364-3703.2008.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Grapevine fanleaf virus (GFLV)‐specific antibodies confer GFLV and Arabis mosaic virus (ArMV) resistance in Nicotiana benthamiana

Abstract: Grapevine fanleaf virus (GFLV) is one of the most destructive pathogens of grapevine. In this study, we generated monoclonal antibodies binding specifically to the coat protein of GFLV. Antibody FL(3), which bound most strongly to GFLV and showed cross-reactivity to Arabis mosaic virus (ArMV), was used to construct the single-chain antibody fragment scFvGFLVcp-55. To evaluate the potential of this single-chain variable fragment (scFv) to confer antibody-mediated virus resistance, transgenic Nicotiana benthamia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 45 publications
0
22
0
3
Order By: Relevance
“…Finally, ELISA readings at OD 405 nm were measured using the Synergy HT reader (BioTek Instruments, Bad Friedrichshall, Germany). The mice with the strongest immune responses were selected for further immunization with 50 lg of protein but no adjuvant and the production of hybridomas as described (Nölke et al 2009). …”
Section: Production Of Monoclonal Antibodiesmentioning
confidence: 99%
“…Finally, ELISA readings at OD 405 nm were measured using the Synergy HT reader (BioTek Instruments, Bad Friedrichshall, Germany). The mice with the strongest immune responses were selected for further immunization with 50 lg of protein but no adjuvant and the production of hybridomas as described (Nölke et al 2009). …”
Section: Production Of Monoclonal Antibodiesmentioning
confidence: 99%
“…The magnetic immunodetection of plant viruses was demonstrated using GFLV as a model. GFLV-specific murine mAbFL 6 was produced using a monoclonal hybridoma cell line (39), and its integrity was verified by SDS-PAGE, followed by staining with Coomassie brilliant blue, and by Western blot analysis. This revealed typical 150-kDa bands under native conditions and separate 55-kDa and 20-kDa bands representing the heavy and light chains, respectively, under denaturing conditions (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, to construct a functional scFv, the influence of the V H and V L orientation on the binding activity and structure should also be considered. Some reports have shown that transgenic plants expressing an scFv that specifically detects plant virus proteins exhibit viral resistance and tolerance (59,60). Therefore, future studies should be performed to examine transgenic plants expressing the broad-spectrum C4 scFv that may achieve wideranging antibody-meditated resistance to potyviruses.…”
Section: Discussionmentioning
confidence: 99%